Fundamental Materials-Issues Involved in the Growth of GaN by Molecular Beam Epitaxy - Nathan Newman; T.C. Fu; Z. Liu; Zuzanna Liliental-Weber; Michael D. Rubin; James S. Chan; Erin C. Jones; Jennifer T. Ross; Ian M. Tidswell; Kin Man Yu; Nathan W. Cheung; Eicke R. Weber (1994)
Gallium nitride is one of the most promising materials for ultraviolet and blue light-emitting diodes and lasers. Both Molecular Beam Epitaxy (MBE) and Metal-Organic Chemical Vapor Deposition (MOCVD) have recently made strong progress in fabricating high-quality epitaxial GaN thin films. In this paper, we review materials-related issues involved in MBE growth. We show that a strong understanding of the unique meta-stable growth process allows us to correctly predict the optimum conditions for epitaxial GaN growth. The resulting structural, electronic and optical properties of the GaN films are described in detail.

Comparison of AIN Films Grown by RF at Magnetron Sputtering and Ion-Assisted Molecular Beam Epitaxy - James S. Chan; T.C. Fu; Nathan W. Cheung; Jennifer T. Ross; Nathan Newman; Michael D. Rubin (Materials Research Society, 1993)
Crystalline aluminum nitride (AlN) thin films were formed on various substrates by using RF magnetron sputtering of an A1 target in a nitrogen plasma and also by ion-assisted molecular beam epitaxy (IAMBE). Basal-oriented AlN/(111) Si showed a degradation of crystallinity with increased substrate temperature from 550 to 770 °C, while the crystallinity of AlN/(0001) Al2O3 samples improved from 700 to 850 °C. The optical absorption characteristics of the AlN/(0001) Al2O3 films as grown by both deposition methods revealed a decrease in sub-band gap absorption with increased substrate temperature.

P-Type Gallium Nitride by Reactive Ion-Beam Molecular Beam Epitaxy with Ion Implantation, Diffusion or Coevaporation of Mg - Michael D. Rubin; Nathan Newman; James S. Chan; T.C. Fu; Jennifer T. Ross (Applied Physics Letters, 1993)
Gallium nitride is one of the most promising materials for ultraviolet and blue light‐emitting diodes and lasers. The principal technical problem that limits device applications has been achieving controllable p‐type doping. Molecular beam epitaxy assisted by a nitrogen ion beam produced p‐type GaN when doped via ion implantation, diffusion, or coevaporation of Mg. Nearly intrinsic p‐type material was also produced without intentional doping, exhibiting hole carrier concentrations of 5×1011 cm−3 and hole mobilities of over 400 cm2/V/s at 250 K. This value for the hole mobility is an order of magnitude greater than previously reported.
Keywords: carrier density; carrier mobility; crystal doping; diffusion; evaporation; gallium nitrides; ion implantation; magnesium additions; molecular beam epitaxy; p−type conductors